Uji kinerja mesin bensin genset dengan campuran bahan bakar RON 90 dan 92 dengan mempergunakan Rem Cakram - Indriyani, Indriyani; Siregar, Zufri Hasrudy; Apollo, Apollo; Andika, Muhammad (universitas teuku umar, 2023)
Fuel oil is the main material used by vehicles in Indonesia. Many fuel processing in Indonesia produces various types of fuel, such as premium pertalite, Pertamax, Pertamax turbo, and diesel, which are often used by generator engines in Indonesia. The purpose of this study was to determine the value of torque, power, and fuel consumption obtained in the generator engine using a mixture of pertalite and Pertamax fuel after using disc brakes. The method used is an experiment using a mixture of pertalite and Pertamax fuel using disc brakes. The results of this research tool can be used as a practicum tool for students majoring in mechanical engineering. The results were obtained at a torque value of 0.39 N/m and power of 0.154 kW in each fuel mixture. This study used a braking load of 0.3 kg with a mixture of pertalite fuel 75% first 25% obtained fuel consumption of 0.00072 kg / h, at a braking load of 0.3 with a mixture of pertalite fuel 65% first x 35% obtained fuel consumption of 0.00065 kg / h, and a braking load of 0.3 kg with a mixture of pertalite fuel 50% Pertamax 50% obtained a power result of 0.00056 kg / h